Robotic-assisted TAPP repair of supraumbilical hernia using the CMR™ Versius robotic system without composite mesh: a case report - Beg, Mirza Faraz; Agrawal, Anirudh; Prakash, Ved; Sharma, Abhisekh (International Surgery Journal, 2025)
Robotic surgery offers improved visualization, ergonomics and instrument dexterity. The CMR™ Versius robotic system presents a promising alternative to traditional platforms for hernia surgery. We report a robotic-assisted TAPP repair for a supraumbilical hernia using the Versius system. Surgical workflow, port placement, mesh deployment and docking time were documented. The surgery was completed without complications using a self-fixating polypropylene mesh, avoiding costly composite materials. The patient recovered uneventfully and was discharged on the second postoperative day. Robotic-assisted TAPP repair using the CMR™ Versius platform is safe, ergonomic and cost-effective. Avoiding fixation devices and composite mesh offers economic advantages. The system holds promise for routine abdominal wall hernia repairs.